Effects of Algal Blooms on Phytoplankton Composition and Hypoxia in Coastal Waters of the Northern Yellow Sea, China - Sun, Xiaohong; Li, Zhao; Ding, Xueyan; Ji, Guanglei; Wang, Lei; Gao, Xiaotong; Chang, Qige; Zhu, Lixin (Frontiers in Marine Science, 2022)
Summer hypoxia and harmful algal bloom occurred sometimes in the nearshore of the northern Yellow Sea in recent years. Based on seven multidisciplinary investigations conducted from March to November 2016, except for April and October, the phytoplankton community and its association with ambient seawater physicochemical parameters in coastal waters of the northern Yellow Sea were comprehensively examined. In total, 39 taxa belonging to 4 phyla and 24 genera were identified. Diatoms and dinoflagellates were the dominant groups, which accounted for 64.1% and 30.8% of total species, respectively. An algal blooming event dominated by the diatom (Thalassiosira pacifica) occurred in March, which affects the shifting of diatom–dinoflagellate dominance. A notable dinoflagellate dominance occurred especially in surface water throughout the whole summer but changed to diatom dominance again from September. Hypoxic zones (<2 mg l-1)were observed in the bottom water in August, with minimum dissolved oxygen (DO) of 1.30 mg l-1. This low DO zone in August was clearly associated with the diatom blooming event (Thalassiosira pacifica) in March, as diatoms in surface waters sank into bottom waters and decomposed by the microbial community resulting in oxygen consumption. After the early-spring diatom bloom, thermohaline stratification occurred and prevented exchanges of dissolved oxygen, which eventually led to hypoxia in bottom waters. The effects of algal blooms on phytoplankton composition and hypoxia could have a cascaded effect on the fishery sustainability and aquaculture in nearshore waters of the northern Yellow Sea.